The The circulation of sars-cov-2 virus inward environment of covid-19 intensive care unit, Dr. Soetomo Hospital Surabaya - Eko B. Koendhori; L. Alimsardjono; S. R. S. Oktaviani; A. M. Widya; Deby Kusumaningrum; Naritha; N. D. Kurniati; P. N. Endraputra; K. Kuntaman (Journal of Clinical Microbiology and Infectious Diseases, 2022)
Introduction: The big problem to overcome COVID-19 transmission is to suppress the viral particle circulation in the air and environment. A severe case of COVID-19 is commonly managed in a negative pressure ICU ward. Covid-ICU room in Dr. Soetomo hospital is a negative pressurized room comprising 5 rooms with an occupancy of 2 beds per room. Meanwhile, the patient’s environment is still possibly contaminated by the virus due to airborne transmission of the virus having tiny particles so the virus can easily spread through the patient’s environment. Thus, the purpose of this study is to evaluate the presentation of the SARS-CoV-2 virus, that was contaminating the room air, floor, and other surfaces inside the Covid-ICU. Method: The study was a cross-sectional descriptive study. The biological sample that analyzes was air. The air samples were taken from all areas including ante-room, patient room, gallery, clothing room, nurse station, and ICU area outside the room using an air sampler (As82 PURIVA H1) with a capacity of 200 m2/hour. The virus filter was put in the port of air entry, after air suction for 2 hours, it was immersed in VTM and continued for rtRT-PCR (real-time Reverse Transcriptase PCR) examination. Surfaces samples were taken by swabbing on the floor, bed cover, door handle, medical equipment, wall, and other equipment. They were swabbed for 5 specimens per location. After data was collected, it analyzes descriptively by using SPSS ver.25 Results: A total of 39 air samples were collected and examined with an RT-PCR machine, 5 (12.8%) positive namely 2 samples from the gallery and 3 from one room, whereas from 30 surfaces, 1 (3.3%) positive, from a sample of the bed cover. Conclusion: The SARS-CoV-2 virus is identified in the air and surface of Covid-ICU wards, indicating the risk for Covid-19 transmission. It is important for Infection Prevention and Control (IPC) policy implementation in a clinical setting.